KORELASI ANTARA LITERASI DIGITAL DENGAN KEMAMPUAN KOMUNIKASI ILMIAH DALAM PEMBELAJARAN FISIKA DI KELAS VIII SMP NEGERI 9 PADANGSIDIMPUAN - Misdiana; Eni Sumanti Nasution; kasmawati (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to determine the correlation between digital literacy and scientific communication ability in physics learning at Grade VIII of SMP Negeri 9 Padangsidimpuan. This research is quantitative research using a correlational method. The population was 120 students, with a sample of 30 students selected using purposive sampling technique. The research instruments used were a digital literacy questionnaire consisting of 25 Likert scale items and a scientific communication ability test in the form of essay questions. Data analysis technique used Pearson Product Moment correlation analysis assisted by SPSS version 25. The results showed that: (1) Students' digital literacy level was in the high category with an average score of 94.97; (2) Students' scientific communication ability was in the good category with an average score of 80.57; (3) There was a positive and significant correlation between digital literacy and scientific communication ability with a correlation coefficient r = 0.718 at a significance level of 5%; (4) The contribution of digital literacy variable to scientific communication ability was 51.6%. The conclusion of the study shows that the higher the students' digital literacy, the higher their scientific communication ability in physics learning.